Fruit on tables - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a room with many long tables. Along the center of these tables are a variety of fruit, including apples, pears, and grapes. Small boxes of Sun Maid raisins are positioned on napkins and on the fruit displays.